Batas Hukum Pembunuhan demi Kehormatan (Honor Killing) dan Religious Vigilantism sebagai Penegakan Moral Privat - Zul Khaidir Kadir (Indo Publishing, 2026)
This article examines how honor killing claims and religious vigilantism operate as forms of private moral enforcement that can distort criminal law’s fact-finding and blame-allocation. Using normative legal research with conceptual and doctrinal approaches, the article builds an operational typology of religious vigilantism along three testable dimensions: (1) enforcement of moral–religious codes, (2) group mobilization and role differentiation, and (3) public spectacle. It then identifies the point of convergence with honor-based homicide in community approval and reputational logic, which jointly function as “social planning” that can be miscast as provocation or mitigation. On this basis, the article proposes doctrinal parameters to prevent moral–communal claims from becoming covert justifications: treating homicide as the baseline qualification, adding a selective hate-crime analogy to capture message/targeting dynamics, and applying collective-violence logic to reach coordinators, instigators, and facilitators. For proof and sentencing, it advances relevance discipline, narrative sanitation, a non-mitigation stance toward community approval, and a public-reason constraint on judicial reasoning so that particular moral doctrines do not undercut equal protection of life. The policy model prioritizes network disruption, incitement, and mobilizing actors under conditions of variable state tolerance and impunity.